Sunset beach [large type] - Andrews, Mary Kay, 1954- (Wheeler Publishing large print hardcover, 2019)
Drue Campbell's life is adrift. Out of a job and down on her luck, life doesn't seem to be getting any better when her estranged father, Brice Campbell, a flamboyant personal injury attorney, shows up at her mother's funeral after a twenty-year absence. Worse, he's remarried - to Drue's eighth grade frenemy, Wendy, now his office manager. And they're offering her a job which she grudgingly accepts. On the bright side, Drue has inherited her grandparents Sunset Beach bungalow. Buth then a suspicious death occurs at a beach resort, exposing possible corruption at her father's firm and making Drue an unwitting investigator. With a budding office romance, a decades-old missing persons case reopened, and a cottage in rehabe, one thing is for sure at Sunset Beach - there's a storm on the horizon..